PENGGUNAAN STRATEGI MIND MAPPING BERBASIS MULTIMEDIA UNTUK MENINGKATKAN HASIL BELAJAR IPS PADA SISWA KELAS V SDN I WONOREJO DEMAK - Triana, Lilis (Universitas Muria Kudus, 2016)
The purposes that want to achoeved in this research are to know the progress of study at 5th gradein society subject that used Mind Mapping base on multimedia strategy. This research applyingclass room action research (PTK) that consisted of two cycles. Research subject are teacher and5th grade students of SDN I Wonorejo Demak that amounted of 29 students. Research result dataobtained throgh observation and test. analysis technique that applied namely descriptivequalitative and quantitative data abalysis technique. Research results show that teacher activityon first cycle as big as 60%, while on second ones teacher activity score increase to 80%. Studentactivity on first cycle as big as 60%, while on second ones teacher activity score increase to 97%.Meanwhile student learning result on first cycle show completeness percentage reach to 59%, andon second cycles improve with classical completeness percentage reach to 86,25%.